Alternatives to Conventional Enterocystoplasty in Children: A Critical Review of Urodynamic Outcomes - González, Ricardo; Ludwikowski, Barbara M. (Frontiers in Pediatrics, 2013)
Alternatives to conventional enterocystoplasty have been developed in order to avoid the most common complications derived from contact of the urine with intestinal mucosa. In this article critically we review the literature on the topics: ureterocystoplasty, detrusorectomy, detrusorotomy, seromuscular gastroenterocystoplasty, use of off the shelf biomaterials, and bladder augmentation by bioengineering. Recognizing the difficulty of deciding when a child with a history of posterior urethral valves requires and augmentation and that the development of a large megaureter in cases of neurogenic dysfunction represents a failure of initial treatment, we conclude that ureterocystoplasty can be useful in selected cases when a large dilated ureter is available. Seromuscular colocystoplasty lined with urothelium (SCLU) has been urodynamically effective in several series when the outlet resistance is high and no additional intravesical procedures are necessary. Seromuscular gastrocystoplasty lined with urothelium seems to offer no distinct advantages and involves a much more involved operation. The use of seromuscular segments without urothelial preservation, with or without the use of an intravesical balloon has been reported as successful in two centers but strict urodynamic evidence of its effectiveness is lacking. The published evidence argues strongly against the use of detrusorectomy or detrusorotomy alone because of the lack of significant urodynamic benefits. Two recent reports discourage the use of small intestinal submucosa patches because of a high failure rate. Finally, research into the development of a bioengineered bladder constructed with cell harvested from the same patient continues but is fraught with technical and conceptual problems. In conclusion of the methods reviewed, only ureterocystoplasty and SCLU have been proven urodynamically effective and reproducible.